Sport, Business, and Sustainability: Trends and Insights from Bibliometric Analysis - Alma, Melek Nur (Sport Economics Research, 2024)
Environmental concerns have increasingly influenced global attention, with both national and international institutions working to address and mitigate their impact. As businesses are central to economic systems, their relationship with environmental sustainability has become a key area of study, particularly within the context of sports. This paper explores the intersection of business, sports, and environmental issues, investigating how these fields have been examined in academic research over time. Using bibliometric analysis, the study identifies key trends, prominent sources, and influential works in this growing area of research. The findings reveal a significant rise in publications over recent years, particularly in the past few years, indicating a strong and increasing focus on sustainable practices in the sports industry. Additionally, the study highlights the dominant role of certain countries and academic institutions in contributing to this field.